(untitled) (Nexus International Journal of Science and Education, 2024)
This qualitative-phenomenological study explored the experiences of elementary teachers in public elementary schools in Compostela East, Davao de Oro, regarding technology-mediated instruction. Employing Creswell's thematic analysis, the research utilized in-depth interviews and focus group discussions as data collection methods, with ten elementary teacher participants chosen through purposive sampling, all with direct experience in employing technology-mediated instruction. The findings revealed that teachers encounter challenges in implementing this instructional approach due to insufficient training for both students and teachers, resource constraints, and the high cost of technology. Despite these hurdles, teachers expressed that seeking support from the school and participating in relevant training programs played a pivotal role in overcoming the challenges associated with technology-mediated instruction. Teachers believed that technology-mediated instruction facilitates connectivity between students and teachers, overcoming barriers of place and time. Moreover, they contended that this instructional approach contributes to students' success, emphasizing the crucial role of teachers' attitudes in its effective implementation. The study recommended that the Department of Education and schools conduct updated training programs focusing on educational technology and relevant trends beneficial for technology-mediated instruction. Additionally, the research suggested ongoing support and monitoring to ensure the sustained effectiveness of this instructional approach in public elementary classrooms.